Exchange rates, credit default swaps and market volatility of emerging markets: Panel CS-ARDL approach - Alan T. Wang; Chin-Chia Liang (Borsa Istanbul Review, 2024)
Using the panel-data approach with a sample of emerging countries, this study examines the relationship between exchange-rate movements from 2011 to 2022, on the one hand, and sovereign debt credit default swap (CDS) premiums and market volatility, on the other. To capture the short- and long-run relationships between exchange rates, sovereign CDS, and market volatility, our study applies the cross-section augmented autoregressive distributed lag (CS-ARDL) model by Chudik and Pesaran (2015) with the pooled mean group (PMG) estimation method. The advantages of this setting are that it allows for cross-sectional heterogeneity and dependence. The exchange rate and the sovereign CDS premium are integrated in the long run. The exchange-rate dynamics, the return on CDS, and market volatility are contemporaneously correlated. Furthermore, market volatility and the deviation from the long-run relationship between the exchange rate and CDS also provide predictive information for exchange-rate movements in the next period. These findings shed further light on the forward-premium puzzle.